Elevated Nitric Oxide Production in Children with Malarial Anemia: Hemozoin-Induced Nitric Oxide Synthase Type 2 Transcripts and Nitric Oxide in Blood Mononuclear Cells - Keller, Christopher C. (American Society for Microbiology, 2004)
Experiments outlined here investigate the role of nitric oxide (NO) in the pathogenesis of Plasmodium falciparum-induced malarial anemia (MA). The results show that ex vivo and in vitro NO synthase (NOS) activity in peripheral blood mononuclear cells (PBMCs) is significantly elevated in children with MA and inversely associated with hemoglobin levels. Additional experiments using PBMCs from non-malaria-exposed donors demonstrate that physiologic amounts of P. falciparum-derived hemozoin augment NOS type 2 (NOS2) transcripts and NO production. Results of these experiments illustrate that elevated NO production in children with MA is associated with decreased hemoglobin concentrations and that hemozoin can induce NOS2-derived NO formation in cultured blood mononuclear cells.